2002
DOI: 10.1007/bf03032394
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mycosis fungoides and its association with EBV and HTLV-1 in Pakistanian patients

Abstract: Mycosis fungoides (MF) is an indolent T cell lymphoma that is distinguished from other lymphomas by its initial appearance on the skin. The histologic diagnosis of MF may be difficult because there is significant overlap in the histologic features of neoplastic T-cell infiltrates and inflammatory dermatoses. This T-cell neoplasm commonly occurs in a mixed, reactive background and can show only a subtle degree of cytologic atypia, rendering histologic diagnosis difficult. In this study MF constituted 0.86% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
6
0
3
Order By: Relevance
“…20,21 The possibility of a common viral etiology can also be entertained especially that viruses such as human T-cell lymphotropic virus type 1 and Epstein-Barr virus have been sporadically/inconsistently linked to MF and KD. 7,22,23 The differential diagnosis of KD in this case included follicular center cell lymphoma. However, the latter was ruled out based on many reasons.…”
Section: Discussionmentioning
confidence: 95%
“…20,21 The possibility of a common viral etiology can also be entertained especially that viruses such as human T-cell lymphotropic virus type 1 and Epstein-Barr virus have been sporadically/inconsistently linked to MF and KD. 7,22,23 The differential diagnosis of KD in this case included follicular center cell lymphoma. However, the latter was ruled out based on many reasons.…”
Section: Discussionmentioning
confidence: 95%
“…[21] A study in Pakistan concluded that the prevalence of MF in Pakistan population is comparable to the Western data, and that Epstein-Barr virus (EBV) and not HTLV-1 association to MF cases was higher than in Western studies. [22] A large study conducted by Bzarachi et al on 127 patients (85 MF, 28 SS, 5 Sézary cell leukemia, 4 lymphomatoid papulosis and 5 unspecified cutaneous T-cell lymphomas) originating from Europe (France, Spain, UK, Portugal) or from USA (California) for the presence of HTLV-1 infection markers obviously point toward that MF and SS were not associated with HTLV-1 infection. [9] In lymphoproliferative disorders, except adult T-cell leukemia (ATL), [23] the seronegativity for HTLV-1 is common.…”
Section: Discussion Discussionmentioning
confidence: 96%
“…EBV was identified in 3 out of 6 cases (50%) by PCR but all these were negative on ISH (EBER). This discrepancy is most likely caused by low copy number of infected cells in tissue sections not amplified as in PCR based studies (Noorali et al, 2002).…”
Section: Ebv and Mycosis Fungoides (Mf)mentioning
confidence: 97%